UNIQUE PROPERTIES OF GRAPHENE - Kudaibergenova Rabiga,; Nurlybayeva Аisha,; Kantarbaeva Saule,; Matniyazova Gulsim,; Sugurbekova G.K.,; Baybazarova Elvira, (Academic Scientific Journal of Chemistry, 2020)
The article is devoted to the unique material graphene (carbon modification), discovered in 2004 by immigrants from Russia Andrei Geim (Andre K. Geim) and Konstantin Novoselov (Konstantin Novoselov), who won the Nobel Prize in physics for this discovery in 2010. Graphene a two-dimensional monoatomic thick carbon block allotrope building, has attracted enormous attention due to its remarkable physical properties and chemical functionalization capabilities. Graphene is a potential nanofiller that can significantly improve the performance of polymer-based composites at extremely low loading. The article is an excursion through the publications of foreign and domestic authors, revealing the unique properties and prospects of using graphene, in particular, in nanotechnology and nanocomposites. Also, this review presents various mechanical, thermal and electrical, as well as other important properties of graphene, which were also discussed along with their potential applications. A graphene-based technical breakthrough is possible because this is the finest substance in the world and can simultaneously possess several very important and unique electronic, electrical properties. Firstly, this substance can be an excellent conductor, since it consists of chains of carbon hexagons, through which electric current is very easily transmitted. Secondly, with some modification, graphene can be an effective insulator. You can make a microcircuit, which consists of conductors, semiconductors and insulators. Each of these characteristics of a substance can be achieved based on graphene.